BLOCKCHAIN EMPOWERED SUPPLY CHAINMANAGEMENT: “ENHANCING TRANSPARENCY, TRACEABILITY, AND EFFICIENCY” - Umme Sania (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Blockchain technology has emerged as a disruptive force with the potential to revolutionize various industries, and supply chain management is no exception. This paper delves into the application of blockchain technology in supply chain management, focusing on its ability to enhance transparency, traceability, and efficiency. By leveraging blockchain, organizations can track the movement of goods in real-time, verify product authenticity, and automate supply chain processes through smart contracts. Through an in-depth analysis of blockchain-based supply chain solutions, this paper explores how blockchain empowers supply chain management by providing transparent tracking of goods, ensuring immutable record-keeping, and streamlining various supply chain processes. By elucidating the potential of blockchain technology in supply chain management, this paper aims to provide insights into how organizations can harness blockchain to transform their supply chain processes and gain a competitive advantage in today’s dynamic marketplace.